Analysis of exosomal competing endogenous RNA network response to paclitaxel treatment reveals key genes in advanced gastric cancer - Lei, Jun; Zhang, Guifeng; Li, Deyu; Zhong, Jiangming; Chen, Qiao; Lin, Li; Liu, Zhenhua (Frontiers in Oncology, 2022)
Background Exosome is an important component of the tumour immune microenvironment and plays critical roles in cancer pathogenesis. Exosome transcriptome of gastric cancer (GC) response to paclitaxel chemotherapy has not been investigated in the past. Methods ceRNA microarrays were performed in exosomes from six advanced GC patients before and after paclitaxel treatment. Bioinformatics tools were used to identify differential expressing genes and construct competing endogenous RNA (ceRNA) network. The importance of hub genes in the ceRNA network were confirmed by survival analysis and functional analysis. Results A total of 213 differential mRNAs, 370 lncRNAs, and 376 circRNAs were identified, and hub genes in ceRNA networks were screened. The differential genes were associated with GO terms SNAP complex, gap junction, protein transporter activity, cytokine receptor, and KEGG pathways synaptic vesicle cycle, propanoate metabolism, Epstein–Barr virus infection, heparin, and steroid biosynthesis, and beta-alanine metabolism. ULK2, CYP2R1, BTLA, and miR-105-5p are prognostic genes for overall survival. Paclitaxel may target ULK2 which is involved in mitosis and cell cycle. miR-105-5p may target ULK2 3’UTR. Conclusion The work for the first time identified exosomal RNA biomarkers and constructed a ceRNA network in GC response to paclitaxel, revealed novel molecular mechanisms of GC, and provided new candidates for GC diagnosis and treatment.